2006
DOI: 10.7705/biomedica.v26i1.1397
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes sociales, prácticas de alimentación y consecuencias nutricionales del parasitismo intestinal en niños de 7 a 18 meses de edad en Guapi, Cauca.

Abstract: Determinantes sociales, prácticas de alimentación y consecuencias nutricionales del parasitismo intestinal en niños de 7 a 18 meses de edad en Guapi, Cauca Introducción. Los estudios de parasitismo intestinal en menores de 2 años raramente se realizan. Sus consecuencias nutricionales y la factibilidad de la prevención justifican su estudio. Objetivos. Identificar la prevalencia de parásitos intestinales patógenos, sus asociaciones con los determinantes sociales y las prácticas de alimentación y sus efectos sob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
1
14
0
13
Order By: Relevance
“…These percentages were low compared to other studies on children in different parts of Colombia and even in international studies concerned with indigenous communities (7,19,(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…These percentages were low compared to other studies on children in different parts of Colombia and even in international studies concerned with indigenous communities (7,19,(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 58%
“…This research has evaluated intestinal parasite prevalence in a sample of 57 children aged 5 and 14 years old from six indigenous communities residing in Cali; the intestinal parasite prevalence found in the indigenous children included in the study was higher than that detected in the world-wide population without ethnic discrimination (6,7). However, this prevalence was lower compared to national reports (8,9). The few national reports would include National Morbidity Research (1965 and 1980) which revealed that helminthiasis caused by Ascaris lumbricoides affected 54 % of the population in 1965, significantly decreasing by 1980 (34 %).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…En este estudio nacional las frecuencias para la zona central para T. trichiura fueron de 35,3 % y para A. lumbricoides de 36,8 % (6). Estos porcentajes son bajos también con relación a otros estudios realizados en otras regiones de Colombia (7,13,14).…”
Section: Discussionunclassified
“…Although the etiology of growth failure is multifactorial, malnutrition and repeated infections in children have been documented as causative agents, among which G. intestinalis is a hallmark cause 16 . Diarrhea, poor sanitation, housing and socioeconomic conditions are factors that contribute to the high prevalence of this parasite 2,3,4,10,46,52 . Moreover, these are nonfood factors that can also be involved in growth failure 2,4,5 .…”
Section: Introductionmentioning
confidence: 99%